Punição, recompensa, persuasão e ajuda: estratégias regulatórias a partir do caso Nota Fiscal Paulista - Paschoal, Bruno Vinicius Luchi (2012)
In 2007, the government of São Paulo created a public policy called the 'Programa de Estímulo à Cidadania Fiscal' (Fiscal Citizenship Enforcement Program), more commonly referred to as the 'Nota Fiscal Paulista' (São Paulo’s VAT Receipt Program) . The program is intended to encourage consumers to request purchase receipts from retailers so that these retailers issue the proper tax documentation when it is solicited. In order to achieve its goals, the program employs a complex system of compensatory and repressive sanctions -- among other strategies -- and involves various social actors, including taxpayers, consumers, and civil society organizations. Using the case study research method, this piece describes and analyzes the Nota Fiscal Paulista program for answers to three main questions: (i) How does Nota Fiscal Paulista work? (ii) How did it come to be?; (iii) What are the regulatory strategies employed to achieve its goals and in what way might those strategies be organized? Pulling together the data and arguments developed in each response to those questions, the work culminates in an empirical discussion of the way in which different types of regulatory strategies were used to construct a contemporary regulatory policy and draw attention to many of its main elements and concepts.